Informal employment in Poland: An empirical spatial analysis - Dagmara Nikulin; Maciej Beręsewicz (Gdańsk University of Technology, Faculty of Management and Economics, 2018)
The main goal of our article is to bridge the gap in the regional analysis of informal employment in Poland and in particular to indicate the propensity for informal work in the working age population, to test if informal activities are typical for marginalized people (less educated, unemployed, older) and to identify the regional and spatial heterogeneity in the propensity. We use data from the "Human Capital Balance 2010-2014" survey. Results indicate a strong relationship between the probability of informal work and age, sex and labour force status. Moreover, a strong spatial dependency can be observed.
Keywords: J21; J46; R12; R23; 330; Informal employment propensity; unregistered work; shadow economy; spatial Bayesian analysis; INLA